Putrescine as a source of instant energy in the small intestine of the rat. Issue 1 (1st January 1998) - Bardócz, S; Grant, G; Brown, D S; Pusztai, A
Abstract : Background and aims —It has been suggested that putrescine acts as a growth factor in the gut, but its exact function in some aspects of cellular metabolism is still in question. The aim of the present work was to identify some functions of putrescine in small bowel metabolism. Animals —Rats (about 80 g), in groups of five, were given either phytohaemagglutinin- or lactalbumin-containing diets, fed ad libitum or were fasted for 48 hours and re-fed for six or twelve hours before being killed. Methods —Uptake of intraperitoneally or intragastrically administered [ 14 C]putrescine and its conversion to succinate by the rat small bowel mucosa was measured. Tissue polyamine and succinate contents were measured by high performance liquid chromatography and amino acid analysis respectively. Results —Uptake of putrescine by the small bowel mucosa from the systemic circulation and conversion of about 30% of this to succinate occurs in the epithelium of the healthy small bowel. Compared with rats given food ad libitum, putrescine uptake was doubled in fasted animals and more than 70% of it was converted to succinate. All these changes returned to control values on refeeding. Using phyto- haemagglutinin induced gut growth as a model, the uptake of putrescine from the systemic circulation by the serosal side of the small intestinal epithelium was increased immediately after growth was stimulated. During phytohaemagglutinin induced growth of the gut, putrescine was converted to succinate in the same proportion as in the healthy small bowel. Conclusions —The experiments identified a novel function for putrescine in gut metabolism: it can be used as an instant energy source when required.